Influence of Preoperative Pain Duration on Microsurgical Varicocelectomy Outcomes - Mustafa Gökhan Köse; Kadir Önem; Mehmet Çetinkaya; Erkan Karadağ; Emre Arpali (Advances in Urology)
Objective. To investigate the question of whether duration of pain before surgery ultimately affects sperm parameters after varicocelectomy. Methods. Fifty patients with painful grade-3 varicocele were investigated prospectively. The patients were divided into two groups according to their symptom period. The patients having had grade-3 varicocele for less than 1 year were included in Group-1 (Ge, n=25). Twenty-five patients who had painful grade-3 varicocele for more than 1 year (Gs, n=25) were classified in Group-2. Semen analysis was performed after 3 days of sexual abstinence twice a month. Total sperm concentration (TSC), rapidly progressive motility (SPa), and slow or sluggish motility (SPb) rates were noted. Pain was evaluated by using 10 cm visual analogue scale (VAS). Results. Postoperative TSC and %SPb were significantly higher in both groups (P=0.01). There was no difference between two groups for preoperative and postoperative TSC, %SPa, % and SPb values. VAS significantly declined in both groups (P=0.005). This postoperative decline was not significant for intergroup comparison. Conclusions. Our results show that increase in semen quality and decrease in the pain after microsurgery varicocelectomy do not depend on the duration of the preoperative pain.